Rheumatological manifestations of infective endocarditis. Issue 5 (October 1984) - Thomas, P; Allal, J; Bontoux, D; Rossi, F; Poupet, J Y; Petitalot, J P; Becq-Giraudon, B
Abstract : A retrospective study showed musculoskeletal manifestations in 32 of 108 patients treated for infective endocarditis in several departments at the Poitiers CHU. Such manifestations included articular pain or aseptic arthritis, typically involving the major joints, as well as vertebral osteomyelitis, low back pain (inflammatory or non-inflammatory), and myalgia. Patients showing such signs were generally younger than those without musculoskeletal involvement, diagnosis was made later, and prognosis was worse; streptococcus D was more often involved, and microscopic haematuria was more common. With the exception of vertebral osteomyelitis, the pathogenesis was not clear.